Detailed grain size analysis of recent Marine sediments and post-glacial history of Port au Port Bay, west Newfoundland - Shearer, James Moxley (1970)
Thesis (M.Sc.)--Memorial University of Newfoundland, 1973. Earth Sciences Bibliography: leaves 190-195.